2000
DOI: 10.1902/jop.2000.71.5.810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diode and Nd:YAG Laser Irradiation on Titanium Discs: A Scanning Electron Microscope Examination

Abstract: From these findings, it was concluded that the diode laser (980 nm) does not damage titanium surfaces, which should be of value when uncovering submerged implants and treating peri-implantitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
3
10

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 25 publications
2
122
3
10
Order By: Relevance
“…The laser-treated surfaces have high biocompatibility, and this is reflected in the clinical studies that have been undertaken to date and produced promising results [89][90][91][92][93][94][95]. …”
Section: Laser-induced Damage To Implant Surfacesmentioning
confidence: 99%
“…The laser-treated surfaces have high biocompatibility, and this is reflected in the clinical studies that have been undertaken to date and produced promising results [89][90][91][92][93][94][95]. …”
Section: Laser-induced Damage To Implant Surfacesmentioning
confidence: 99%
“…In dentistry, Nd:YAG lasers are indicated for soft-tissue surgeries such as gingivectomy, periodontal sulcular debridement, laser-assisted new attachment procedures (LANAP), frenectomy, biopsy, and coagulation of graft donor sites (57,60,61). These lasers are contra-indicated for peri-implant procedures as they easily cause melting of the titanium surfaces of dental implants (62). As the laser light of Nd:YAG lasers is selectively absorbed by dark colors, clinicians frequently paint a coating of black dye or paste on the target area before exposing it to the laser in order to enhance the absorption The use of titanium dioxide (TiO 2 ) pigment as an alternative to the black dye has also been historically studied (63).…”
Section: Basic Properties Of Carbon Dioxide (Co 2 )mentioning
confidence: 99%
“…It was observed that 980 nm diode did not cause any surface alterations on the titanium surface irrespective of the power settings or the pattern. 18 Moritz et al showed that up to 96.9% bacteria could be eliminated with an 810 diode at 2.5 W, 50 Hz at pulse duration of 10 ms with a 0.4 mm tip. 19 Significant bacterial reduction was seen even at low levels of irradiance with low energy diode lasers.…”
Section: Diodementioning
confidence: 99%